The Alexandrian Epistle of Jude - Gunther, John J. (New Testament studies, 1984)
The hypothesis of Jude's Alexandrian origin, which was set forth by Ernst Th. Mayerhoff in 1835 and has been supported by D. Schenkel, W. J. Mangold, H. Holtzmann, O. Pfleiderer and James Moffatt, deserves to be revived.Its associations with Syria and Palestine are superficial. Although the Apostolic Constitutions (Apost. Canon 85) canonizes all of the Catholic Epistles, it was not until the early sixth century that Philoxenus brought Jude into the Syriac canon. Eusebius (hist.eccl. ii,23.25; iii,25.3) placed it among the disputed writings. J. N. D. Kelly deems it unlikely that the readers ‘were converts from Palestinian Judaism, for the Gnostic libertinism attacked cannot have had much attraction for people brought up to reverence the Law’. There is no evidence that libertine Gnostics ever were a problem anywhere in Syria either. There is no point of contact between Jude and either the Judas Thomas apocrypha or Ignatius or the Docetic and Judaizing errors he opposed at home or on the road. Hans Windisch remarked that the suppression of the blood relationship of Judas with Jesus bespeaks the non-Palestinian origin of the letter. The readers of the epistle did respect both Judas and James, who represented Palestinian dynastic Christianity. But such esteem did not prevail at Antioch (Acts 15.1; Gal. 2. 12) or where Matthew (12. 46–50) and Mark (3. 31–35), with their bias against the Lord's brothers, were written. The Synoptic Gospels did not influence Jude. The remoteness of Rome and the West from Judaean Christianity argues against any association with our epistle. Neither 1 Clement nor the Shepherd of Hermas reveals an awareness of the problems with which Jude deals. The epistle has nothing in common with Revelation or Asian millenarianism; Papias did not even include Judas in his list of disciples. Justin's ignorance of Jude tends to forbid its connection with Ephesus or Rome.